Risks of frost in potato crops in the region of Guarapuava-PR in different phases of ENSO (Research, Society and Development, 2020)
The cultivation of crops under conditions of low predictability of climatic variability can be considered as an element of significant reduction in production results. The potato is defined as a crop that is sensitive to intense cold, and the cultivation cycle can occur in a period of risk of frost events. In the south of Brazil in different phases of the ENSO (El Niño-Southern Oscillation), La Niña, El Niño or in climatic neutrality, oscillations occur in climatic normals, including minimum temperatures. Thus, the study aimed to assess the risks of the occurrence of frosts of different intensities during the potato crop development cycle, at different planting periods in Guarapuava-PR, in different ENSO phases and in climate neutrality. A 43-year historical series of climatic data between 1976 and 2018 was used. The analyzes were performed using descriptive statistics using percentage indexes and normalization of the data set. The data were grouped in december periods for the months of August to October and March to May, when there is a frequency of frosts and the possibility of potato crops under development in the field. Among the main results it was found that the planting period, with the minimization of the risk of frosts occurring in the potato crop for the region of Guarapuava, is comprised between September 21 and January 31 in both phases of ENSO, El Niño and La Niña and Climate neutrality. In general, potato cultivation in years of neutrality is subject to greater risks of losses due to frost when compared to planting in years of El Niño and La Niña phenomenon.